The Synergistic Role of Diet and Exercise in the Prevention, Pathogenesis, and Management of Ulcerative Colitis: An Underlying Metabolic Mechanism. (March 2019) - Stavsky, Jonah; Maitra, Radhashree
Ulcerative colitis (UC) is a biologically complex condition characterized by chronic, relapsing inflammation of the gastrointestinal tract. The relative incidence of this debilitating condition is increasing and sociologically damaging outcomes are a continued reality. Several etiological theories for UC are currently under investigation, spanning between genetic and environmental determinants. From an environmental perspective, previous literature reviews have demonstrated the independent effectiveness of specific diet and exercise patterns in modifying UC immuno-pathophysiology. This article explores the synergistic role of diet and aerobic exercise in the prevention, pathogenesis, and management of UC in the context of recent immunological research. Through a unifying mechanism—that is, microbial influence of colonic inflammation and immuno-pathophysiology—the simultaneous reduction of pro-inflammatory dietary sulfurous amino acid intake (ie methionine, cysteine, homocysteine, and taurine) and the upregulation of aerobic exercise frequency (which spurs the colonization of anti-inflammatory butyrate, acetate, and propionate producing microbial taxa) demonstrate the clinical efficacy of incorporating both diet and exercise modifications for UC prevention and management through pathogenic alterations.